Hubungan Diplomatik Malaysia-Jepun, 1957-1970-an: Satu Analisis - Lazim, Ahmad Sohaimi (Perspektif Jurnal Sains Sosial dan Kemanusiaan, 2010)
<span style="display: inline !important; float: none; background-color: transparent; color: #000000; font-family: 'Helvetica Neue',Helvetica,Arial,sans-serif; font-size: 12px; font-style: normal; font-variant: normal; font-weight: 500; letter-spacing: normal; line-height: 13.2px; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">Japan was defeated in the Second World War in 1945. Although the Japanese occupation in Malaya was only for the period of three years and eight months, it left behind traumatic experiences for the people of Malaya. However, diplomatic relations between the two countries continued to progress after Malayan (later Malaysia) independence. During the early stages of their relations, both were concerned about their economic activities and tried to cooperate with each other so as to gain profitably from their relationship. Japan was to get supplies of raw materials and able to market their products in Malaysia. But the latter was a developing country and needed financial and technological assistance from Japan. Hence, the economic relationship between Malaysia and Japan was rather unbalanced. As an advanced country, Japan took advantage of and exploited the cheap raw materials and sales of consumer products in Malaysia. Japan offered credit assistance and investments, but at the same time they received almost a million economic projects in Malaysia. It meant that Japanese foreign policies to help the developing countries through their ODA (Overseas Development Assistance) had other ulterior motives. Malaysia and other Southeast Asian countries were very dissatisfaid with the Japanese approach to create economic assistance. Later Japan changed some policies which gave more importance to the needs and requirements of the Asean countries, including Malaysia. In 1980’s when Dr. Mahathir became Prime Minister there was much improvement in the economic cooperation between Malaysia-Japan, especialy with the introduction of his Look East Policy in 1982.